Cytokine Profiles of Head and Neck Squamous Cell Carcinoma Undergoing Dual Immunotherapy With Cetuximab and Pembrolizumab Identify Interferon Gamma-Induced Protein 10 as Novel Biomarker - Berszin, Michael; Michaelides, Ioannis; Siemert, Julia; Röhl, Louisa; Wellhausen, Jana; Wald, Theresa; Bohr, Christopher; Künzel, Julian; Gradistanac, Tanja; Dietz, Andreas; Zebralla, Veit; Pirlich, Markus; et al. (Frontiers in Oncology, 2022)
Background: Pembrolizumab and cetuximab are antibodies under investigation in head and neck squamous cell carcinoma (HNSCC) either as single agents or combined with cisplatin and other chemotherapeutic drugs, e.g. 5-fluorouracil and/or docetaxel. However, also the combination of both antibodies may have potential in recurrent/metastatic (R/M) HNSCC, in particular in cisplatin-resistant or -refractory cases or patients with comorbid disease, e.g. patients with impaired renal function. Methods: To clarify potential benefit that may result from such combination, we used the FLAVINO assay, a short-time ex-vivo assay to compare responsiveness of HNSCC to pembrolizumab, cetuximab and both combined regarding colony formation of epithelial cells of biopsy-derived tumor samples and their cytokine production within three days either without or with stimulation with 10 ng/mL interferon gamma (IFN-γ). Vascular endothelial growth factor A (VEGF), monocyte chemoattractant protein 1 (MCP-1 or CCL2), interleukin 6 (IL-6), IL-8, IFN-γ, and interferon-gamma induced protein 10 (IP-10 or CXCL10) in supernatants were measured by ELISA. Results: We detected huge heterogeneity in response to cetuximab, pembrolizumab and both combined with and without IFN-γ stimulation. Moreover, we detected a link between IFN-γ induced IP-10 release and improved outcome in those HNSCC patients who were capable to respond to IFN-γ and pembrolizumab, cetuximab and both combined with a further increase in IP-10 production. We derived an “IP-10 score” that independent from clinical characteristics of HNSCC patients and therapy regimens applied was able to predict their outcome. Conclusions: The heterogeneity in the ex-vivo response of cetuximab, pembrolizumab and both combined with and without IFN-γ stimulation identifies subgroups of HNSCC patients with deviating OS.